КАЛІБРУВАННЯ ТЕРМОЕЛЕКТРИЧНИХ СЕНСОРІВ ТЕПЛОВОГО ПОТОКУ В СИСТЕМАХ ДІАГНОСТУВАННЯ ТЕПЛОВОГО СТАНУ ЕЛЕКТРИЧНИХ МАШИН - Бабак, В.П.; Ковтун, С.І. (Інститут електродинаміки НАН України, Київ, 2019)
Prospects and specific features of the application of thermoelectric heat flow sensors in the systems of diagnostics of the thermal state of electric machines are considered. A method for calibrating sensors is improved by implementing a step-by-step procedure, in resulting the verification procedure without demounting the sensor and can be carried out at the site of operation. The correction factor for the refinement of the conversion factor under operating conditions was determined. The correction is a characteristic of the heat flow sensor and depends on the design, technological and thermophysical parameters of a particular sensor instance that was placed to the heat exchange conditions characteristicfor the study object. References 8, figure 1.